Respuesta :
Answer:
The equation is a contradiction: it has no solutions
Step-by-step explanation:
5(+2)−6(2−)=+10(+1)
5(x+2)−6(2−x)=x+10(x+1)5(x+2)-6(2-x)=x+10(x+1)5(x+2)−6(2−x)=x+10(x+1)
Solve
Distribute
5(+2)−6(2−)=+10(+1)
5+10−6(2−)=+10(+1)
Rearrange terms
Distribute
Subtract the numbers
Combine like terms
Distribute
Combine like terms
Add
2 to both sides of the equation
Simplify
Subtract 11 from both sides of the equation
Simplify
Result
0=12
Answer:
x = -11 (sorry if this is wrong)
Step-by-step explanation:
5(x+2)-6(2-x)=10(x+1)
5x +10 -12x + 6x = 10x + 10
-1x + 10 = 10x + 10
-10x -10x
-11x + 10 = 10
-10 -10
-11x = 0
---- ----
-11 -11
x = -11